Portrait of the Management of Tenganan Pegeringsingan Traditional Village - DARMAWAN, Nyoman Ari Surya; SANCAYA, I Wayan Werasmana (PT Batara Swastika Harati, 2024)
The village regulations (awig-awig) of Tenganan Pegeringsingan Traditional Village are supported by the 1945 Constitution and the Provincial Regulation of Bali, thus giving them clear legal authority. These regulations serve to organize, protect, resolve conflicts, and guide the entire community, as well as to develop cultural values that align with local traditions. Although traditional villages are generally seen as social organizations based on the Kahyangan Three and the Tri Hita Karana philosophy, Tenganan maintains a strong adherence to the Rwabhineda philosophy, which originates from the pre-Hindu era. The authority of the traditional village demonstrates a claim of superiority over autonomous power. This autonomy is essentially a reflection of an anthropological construct that has evolved over centuries. Additionally, such regulations automatically provide social control for the Tenganan Pegeringsingan Traditional Village, both preventively and curatively. Organizationally, Tenganan Pegeringsingan has its own leadership mechanism characterized by authenticity and seniority, which fosters a democratic climate. Although seniority is the basis for determining positions, the traditional council does not act arbitrarily. There is a mechanism called